2002
DOI: 10.1159/000063647
|View full text |Cite
|
Sign up to set email alerts
|

Who Develops Acute Stress Disorder after Accidental Injuries?

Abstract: Background: Acute stress disorder (ASD) is still a much discussed diagnosis, and research on predictors of ASD is sparse. The aim of this study was to assess the prevalence of ASD in a random sample of accident victims and to investigate the associations between different independent variables and ASD symptomatology with the objective to find a regression model best explaining the variance in ASD symptom level. Methods: We collected a randomized sample of hospitalized accident victims (n = 323). ASD was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
4
25
1
Order By: Relevance
“…The high SOC scores in the LSG correspond to the concept of the SOC as an indicator for an individual’s capacity to adequately respond to a stressor by means of appropriate and diverse coping strategies and is in accordance with the literature [3, 41]. Patients scoring high on the SOC can probably accept their situation better than those with low SOC scores.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The high SOC scores in the LSG correspond to the concept of the SOC as an indicator for an individual’s capacity to adequately respond to a stressor by means of appropriate and diverse coping strategies and is in accordance with the literature [3, 41]. Patients scoring high on the SOC can probably accept their situation better than those with low SOC scores.…”
Section: Discussionsupporting
confidence: 85%
“…We have reported that the patients’ appraisal of the severity of their accident, and of their ability to cope with the accident, made a substantial contribution to their time off work due to the accident, independent of the objective severity of the injuries [45]. This finding is consistent with results of another sample of accident victims [3], and highlights the importance of subjective factors in the pathogenesis of posttraumatic disturbances. Malt [6] stated that it is the personal meaning and the implication of the injury, rather than external threats that are crucial for the ongoing appraisals and thus ultimately for coping.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Since no validated assessment tool for ASD was available at the time of this study, ASD symptoms were assessed using a combination of items from the CAPS and the Peritraumatic Dissociative Experiences Questionnaire (PDEQ) (Fuglsang et al 2002). The PDEQ rater version (Marmar et al 1997) is a 10-item interview for the assessment of peritraumatic dissociation.…”
Section: Main Outcome Variablesmentioning
confidence: 99%
“…By this procedure an ASD score was obtained with a maximum range from 0 to 17 which showed a satisfactory internal consistency [Cronbach's alpha =.68; for further details see 35].…”
Section: Peritraumatic Dissociative Experiences Questionnaire Rater mentioning
confidence: 99%